2020
DOI: 10.7454/ihpa.v5i3.3180
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden Bore by Patients and Families because of stroke: Policy Assessment

Abstract: Stroke to this day is still a disease that causes a high disability. In the future, it will require a prohibitive cost so that it has an impact on the socio-economic consequences for patients and their families. The price is prohibitive so that the impact on socioeconomic implications for patients and their families. Because of that, the purpose of the study is to estimate the cause of the cost that causes an economic burden from a stroke. The method that is used is a content analysis by doing a further litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The economic burden for treatment and rehabilitation, as well as additional costs, are very high. 6,7 The burden of ischemic stroke disability is exacerbated by the frequent incidence of ischemic stroke in elderly individuals as well as in the unemployed. 8 The World Health Organization's (WHO) International Classification of Functioning, Disability, and Health (ICF) stated that neurological disorders can have three effects, changes in body structure and function (impairment), daily and instrumental activities, and taking part in life roles (work, family, fun, and travel).…”
Section: Introductionmentioning
confidence: 99%
“…The economic burden for treatment and rehabilitation, as well as additional costs, are very high. 6,7 The burden of ischemic stroke disability is exacerbated by the frequent incidence of ischemic stroke in elderly individuals as well as in the unemployed. 8 The World Health Organization's (WHO) International Classification of Functioning, Disability, and Health (ICF) stated that neurological disorders can have three effects, changes in body structure and function (impairment), daily and instrumental activities, and taking part in life roles (work, family, fun, and travel).…”
Section: Introductionmentioning
confidence: 99%
“…Data from Basic Health Research (Riset Kesehatan Dasar/Riskesdas) in 2018 found that the prevalence of stroke had reached 10.9 per 1,000 population, compared to 7 per 1,000 in 2013. 1,2 Stroke is also the highest cause of mortality in hospitals, resulting in 15.4% of all hospital deaths in the population over the age of 5 years. 3 The sequelae of stroke cause high morbidity among stroke survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Beside those factors, irregular medical check up and obesity also as key factors for increasing recurrent stroke incidence in Indonesia [5]. During the first period of inhospital care, one hemorrhage stroke patient need approximately 13.8 billion rupiah and totally around 622 billion rupiah for 45 period of care [6], [7].…”
Section: Introductionmentioning
confidence: 99%